Zachowania zdrowotne i urazy sportowe = Health behaviors and sport injures - Weber-Rajek, Magdalena; Bethke, Anna; Radzimińska, Agnieszka; Lulińska-Kuklik, Ewelina; Zukow, Walery (Journal of Education, Health and Sport, 2016)
Weber-Rajek Magdalena, Bethke Anna, Radzimińska Agnieszka, Lulińska‑Kuklik Ewelina, Zukow Walery. Zachowania zdrowotne i urazy sportowe = Health behaviors and sport injures. Journal of Education, Health and Sport. 2016;6(5):119-130. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.51331 http://ojs.ukw.edu.pl/index.php/johs/article/view/3514 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.04.2016. Revised 29.04.2016. Accepted: 11.05.2016. Zachowania zdrowotne i urazy sportowe Health behaviors and sport injures Magdalena Weber-Rajek1, Anna Bethke2, Agnieszka Radzimińska1, Ewelina Lulińska‑Kuklik3, Walery Zukow4 1. Katedra Fizjoterapii, Zakład Podstaw Fizjoterapii, Collegium Medicum w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu 2. Bydgoska Szkoła Wyższa w Bydgoszczy 3. Akademia Wychowania Fizycznego i Sportu w Gdańsku 4. Uniwersytet Kazimierza Wielkiego w Bydgoszczy Słowa kluczowe: zachowania zdrowotne, uraz sportowy. Keywords: health behaviors, sport injury. Streszczenie Jednym z najważniejszych elementów zdrowego trybu życia jest sprawność fizyczna. Dlatego też grupą osób, która, jak mogłoby się wydawać, najbardziej opiera swoje życie na zachowaniach zdrowotnych są sportowcy. Badaniami objęto 100 osób (68 mężczyzn i 32 kobiety) w wieku od 18 do 30 lat (średnia wieku 21,41) różne dyscypliny sportowe: siatkówkę (n=32); koszykówkę (n=34); piłkę nożną (n=34). W badaniach wykorzystano Inwentarz Zachowań Zdrowotnych Zygfryda Juczyńskiego oraz ankietę autorską. W całej badanej grupie wykazano średni poziom zachowań zdrowotnych. Ze wszystkich kategorii zachowań zdrowotnych najwyższy wynik uzyskano w kategorii „pozytywne nastawienie psychiczne”, najniższy w kategorii „prawidłowe nawyki żywieniowe”. Wyniki kobiet były wyższe od wyników mężczyzn. W badanej grupie nie wykazano istotnej statystycznie różnicy w zachowaniach zdrowotnych, u których w przeciągi 12 miesięcy wystąpiły urazy, w stosunku do osób bez urazów. Summary One of the most important elements of health behaviors is physical fitness. Therefore, a group of people, which, as you might think, most based his life on health behaviors are athletes. The study involved 100 people (68 men and 32 women) aged 18 to 30 years (mean age 21.41) different sports: volleyball (n = 32); basketball (n = 34); football (n = 34). The study used Inventory Behavioral Health by Juczynski and author's questionnaire. In the whole group was shown the average level of health behavior. Of all the categories of health behavior achieved the highest score in the category of “positive psychological attitude”, the lowest in the category of “proper nutrition habits”. The results for women were higher than men results. In the study group showed no statistically significant difference in health behaviors, in which the drafts were injuries 12 months, compared to those without injury.